Galicio-portuguese oak forest of Quercus robur and Quercus pyrenaica:biodiversity patterns and forest response to fire - Proença, Vânia (2009)
Tese de doutoramento, Biologia (Ecologia), 2009, Universidade de Lisboa, Faculdade de Ciências